Development of a novel osmotic membrane bioreactor for water reclamation - Lay, Winson Chee Loong (2012)
The study focused on the development of a novel osmotic membrane bioreactor (OMBR) for water reclamation. It was found that stable water production under elevated mixed liquor concentration could be achieved. The OMBR achieved organic removal and pharmaceutical removal in excess of 99% and 96%, respectively. However, the biological process was critical to the overall performance of the OMBR. Salt accumulation and flux performance are key issues for OMBR, whereby membrane fouling plays a significant role, such that mild fouling may have ameliorating effects, whereas severe fouling may have aggravating effects. New methods of assessing OMBR performance were developed. Experiments verified that the OMBR could achieve stable flux and good product quality at recovery up to 95.8% with flux efficiency factor ≥ 0.8. The study substantiated that the OMBR is a potential technology for water reclamation. However, there are important performance-affecting factors that need to be further researched.